2005
DOI: 10.1021/ac050455c
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Assessment of Human Liver Transplants from Biopsy Samples at the Donor and Recipient Stages Using High-Resolution Magic Angle Spinning 1H NMR Spectroscopy

Abstract: This work presents the first application of high-resolution magic angle spinning (HR-MAS) 1H NMR spectroscopy to human liver biopsy samples, allowing a determination of their metabolic profiles before removal from donors, during cold perfusion, and after implantation into recipients. The assignment of peaks observed in the 1H HR-MAS NMR spectra was aided by the use of two-dimensional J-resolved, TOCSY and 1H-13C HMQC spectra. The spectra were dominated by resonances from triglycerides, phospholipids, and glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 34 publications
5
79
0
Order By: Relevance
“…Further MRI studies in vivo have demonstrated a close relation between hepatic steatosis and body adiposity, and a close correlation between MRI estimation of adiposity and histological assessment in two of these patients [11] . Although studies have shown a close association between in vivo estimates and biopsies, in vitro MRS assessment of lipid content in liver biopsies by MAS MRS would allow direct comparison with histology, reducing the effect of sampling error [33] .…”
Section: Hepatic Steatosismentioning
confidence: 99%
See 2 more Smart Citations
“…Further MRI studies in vivo have demonstrated a close relation between hepatic steatosis and body adiposity, and a close correlation between MRI estimation of adiposity and histological assessment in two of these patients [11] . Although studies have shown a close association between in vivo estimates and biopsies, in vitro MRS assessment of lipid content in liver biopsies by MAS MRS would allow direct comparison with histology, reducing the effect of sampling error [33] .…”
Section: Hepatic Steatosismentioning
confidence: 99%
“…In a preliminary study, Duarte and colleagues used in vitro 1 H MAS MRS to assess biopsies taken at three time-points from six livers, before removal from donors, during cold perfusion and following implantation into the recipient [33] . The biopsies with the highest concentration of peaks reflecting fatty acyl chain (triglyceride) resonances were also identified as those also estimated to have the highest fat content on histological analysis.…”
Section: Orthotopic Liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the past few years, metabonomics has shown enormous potential for use in disease diagnosis, toxicological mechanism research and the identification of biomarkers [3][4][5][6][7][8]. Nowadays, many techniques have been employed in metabonomic studies, such as nuclear magnetic resonance (NMR) [9][10][11][12][13][14][15], gas chromatography/mass spectrometry (GC/MS) [16][17][18] and liquid chromatography/mass spectrometry (LC/MS) [19][20][21]. Most recently, a new LC/MS technology known as ultraperformance liquid chromatography (UPLC) coupled with Q-TOF MS detection has been used widely in metabonomic studies [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…With some spectral editing techniques [27] , one can also separate signals of metabolites according to their physical properties without separating samples [15,27,28] . With high resolution magic-angle spinning NMR and in vivo magnetic resonance techniques, the metabolites in biological tissues can also be analyzed which are exemplified in a number of studies of biological tissues such as the liver [9,19,[28][29][30] and intestine [31,32] .…”
Section: Introductionmentioning
confidence: 99%